Enterococcus faecalis virulence regulator FsrA binding to target promoters - Del Papa, María Florencia (2011)
The FsrABDC signal transduction system is a major virulence regulator in Enterococcus faecalis. The FsrC sensor histidine kinase, upon activation by the gelatinase biosynthesis-activating pheromone (GBAP) peptide encoded by the fsrBD genes, phosphorylates the FsrA response regulator required for the transcription of the fsrBDC and the gelE-sprE genes from the fsrB promoter and the gelE promoter, respectively. FsrA belongs to the LytTR family of proteins, which includes other virulence regulators, such as AgrA of Staphylococcus aureus, AlgR of Pseudomonas aeruginosa, and VirR of Clostridium perfringens. The LytTR DNA-binding domain that characterizes these proteins generally binds to two imperfect direct repeats separated by a number of bases that place the repeats on the same face of the DNA helix. In this study, we demonstrated that FsrA also binds to two imperfect direct repeats separated by 13 bp, based on the consensus sequence of FsrA, T/AT/CAA/GG GAA/G, which is consistent with the binding characteristics of LytTR domains.